Comparative studies on plutonium utilization in HTTR with helium and carbon dioxide gas coolants. (11th May 2016) - Waris, Abdul; Prastyo, Puguh Andik; Pramuditya, Syeilendra; Irwanto, Dwi; Sekimoto, Hiroshi
Abstract: A high temperature engineering test reactor (HTTR) has been developed and constructed by Japan Atomic Energy Research Institute (JAERI) since 1990s. The standard HTTR has been designed for helium coolant with thermal energy output of 30 MW. HTTR uses graphite as the moderator with outlet coolant temperature of 950 °C. Instead of the pebble-bed type of fuel, the prismatic block fuel type with low enriched UO2 has been employed in this reactor. In this study we have performed comparative evaluations on plutonium oxide utilization in uranium fuel cycle of HTTR with helium gas and carbon dioxide gas coolants. The cell-burnup calculations have been performed by using a SRAC 2006 code, with the nuclear data library was derived from JENDL3.3. The 3-dimensional calculations were performed by employing a CITATION code. The results show that the reactor can achieve its criticality condition if the plutonium concentration in the loaded fuel is 5.0% or higher for both coolant materials. Highlights: The comparative evaluation on PuO2 utilization in uranium fuel of HTTR with He and CO2 gas coolants has been conducted. The cell-burnup calculations have been performed by using a SRAC 2006 code, with nuclear data library is JENDL3.3. The 3-dimensional calculations were performed by employing CITATION code. HTTR can obtain its criticality if the plutonium fraction in the loaded fuel is ≥5.0% for both of coolants.